Improvement of a novel heat pipe network designed for latent heat thermal energy storage systems. (5th September 2016) - Mahdavi, Mahboobe; Qiu, Songgang; Tiari, Saeed
Highlights: Investigation of the effects of heat pipe network configuration on its performance. Modeling of combined vapor jet impingement and vapor condensation. Optimized geometry to alleviate flow separation and improve the performance. Study of the effects of condenser inlet shapes and adiabatic section locations. Best performance was achieved with concentric adiabatic section configuration. Abstract: In the present work, the performance of a heat pipe network designed for a latent Thermal Energy Storage unit in a Concentrating Solar Power System was investigated numerically. A two-dimensional axisymmetric model was implemented to describe the vapor flow and heat transfer inside the vapor core. The network consists of a primary heat pipe and a concentric secondary heat pipe. The solar energy impinges on the disk shaped evaporator is transferred to the heat engine through adiabatic section. The excess heat is used to charge the phase change material via the secondary concentric heat pipe. The vapor flow leaving the adiabatic part of the primary heat pipe to the main condenser is similar to the confined jet impingement. As the flow impinges on the surface and spreads out radially, several recirculation zones have formed, resulting in non-uniform condensation on the condenser surface. The objective of the current work is to optimize the geometry of the heat pipe to alleviate flow separation and hence to improve the performance of the heat pipe. The effects of main condenser and secondary heat pipe entrance shapes on streamline contours, pressure and temperature distributions of the main condenser and secondary heat pipes were investigated. The impact of the primary heat pipe position was studied. Two configurations studied are center located adiabatic section and outward positioned adiabatic section. The performance of the heat pipe was evaluated by calculating the corresponding thermal resistances. For a case with tubular adiabatic section, the result showed that the condensers inlets shapes do not have significant effects on the recirculation zone configuration, but only shift up the pressure and temperature distributions of the main condenser and the secondary heat pipe. Among the various shapes studied for the main condenser inlet, tapered inlet results in the lowest thermal resistances for both the main and secondary condensers. It was also concluded that locating the adiabatic section of the primary heat pipe outwards reduces the size and quantity of the recirculation zones and dramatically increases the average temperatures of the condensers. Tapering the main condenser entrance eliminates the primary recirculation zone, resulting in a uniform temperature distribution inside the main condenser.